LITERATURE REVIEW : Efektivitas Transcutaneous Electrical Nerve Stimulation Dan Slow Reversal Hold Exercise Dalam Meningkatkan Range Of Motion Knee Pada Penderita Osteoarthritis Lutut - Yusfahlis Abdul Rozak (2020)
Objective: Increasing Range of Motion in patients with knee osteoarthritis is influenced by the number of elderly population over 60 years, so that the case of musculoskeletal in the elderly namely osteoarthritis of the knee is increasing. Hold Exercise in Increasing Range of Motion Knee in Patients with Knee Osteoarthritis. Methods: Search for references from internet files, journals, books, etc. that are relevant to research, search for journals using the Google Scholar portal, E-Resources of the National Library, Pubmed, Scient Direct, Jospt, etc. analysis of journals in the worksheets of the results of analysis with a time span of publication in 2015-2020. Literature search found as many as 8 articles analyzed through analysis of topic suitability, research methods used, interventions, samples, instruments / parameters. Results: After reviewing the literature as many as 8 articles show that Transcutaneous Electrical Nerve Stimulation and Proprioceptive Neuromuscular Fascilitation (PNF) modification of Slow Reversal Hold are effective to increase ROM and reduce pain in the knee. Conclusion: That Intervention of Transcutaneous Electrical Nerve Stimulation and Slow Reversal Hold is very effective to increase ROM and reduce pain in patients with knee osteoarthritis significantly.